Aspects of regional history Ilhéus-BA as a source of content for the teaching of physics (International Seven Journal of Multidisciplinary, 2024)
In this article, we recover the history of an old hydroelectric power station in the rural area of the city of Ilhéus - BA through documentary analysis and interviews. We go on to offer suggestions for working with physics and technology concepts for elementary school science teachers, which can also be extended to high school physics. Although the content is of great regional relevance, our idea can be used to study relevant information for science teaching in other locations. We based our study on the CTS (Science, Technology and Society) approach to science teaching. The perspective we adopted emphasizes scientific literacy with a view to citizenship, against the backdrop of the social importance of the subject. We also draw attention to the recovery of the history and culture of a region for the teaching of physics and technology within this framework. Finally, we suggest strategies for teaching physics in accordance with the PCN (National Curriculum Parameters) for Natural Sciences for the final years of elementary school.